IMPOLITENESS IN THE ONLINE GAME FREE FIRE HIGH CLASS STUDENTS OF SDN KURISA PRAGMATIC STUDIES - Dina Karina; Yunidar; Mohammad Tahir; Ulinsa; Juniati (Universitas Muhammadiyah Makassar, 2026)
The rapid development of digital technology has transformed online games into new spaces for social interaction among children, including elementary school students. One of the most popular online games is Free Fire, which provides real-time communication features through voice chat and text chat. Such interactions potentially encourage language use that deviates from norms of politeness. This study aims to describe the forms of linguistic impoliteness and to identify the factors influencing impolite language use among upper-grade students at SDN Kurisa in their engagement with the online game Free Fire. The research employed a qualitative descriptive approach within a pragmatic framework. The data consisted of students' utterances collected through voice chat recordings, screenshots of in-game text chats, classroom and field observations, and semi-structured interviews with students, teachers, and parents. Data analysis was conducted using Culpeper's theory of impoliteness, encompassing strategies such as bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock politeness, and withhold politeness. The findings indicate that students frequently produced impolite utterances in the form of insults, profanity, direct commands without mitigation, sarcastic remarks, and the use of harsh slang and gaming jargon. These practices were influenced by internal factors, including limited emotional control and insufficient awareness of politeness norms, as well as external factors such as the competitive nature of the game, peer group influence, and weak social control in digital environments. The study also reveals a tendency for language practices from the gaming context to transfer into everyday school interactions. This research contributes to pragmatic studies on impoliteness in children's digital communication and offers practical implications for teachers and parents in fostering polite language use in the digital era.